Humanities education reform exploration and practice under outcomes-based education (OBE) - P. Yang (Образование и наука)
Introduction. The concept of outcomes-based education (OBE) was first put forward in 1981 by the educator W. Spady, and has been widely valued and applied in a rapid speed. During the next 10 years, OBE has formed a relatively complete theoretical system and became the mainstream ideas of national education reform in the United States, Britain, Canada and other counties. At present, the technology and tools of OBE, despite the criticism, remain relevant for the development and optimisation of the humanities education system.The aim of the present research is to study and analyse the theory of OBE and the practice on the application of pedagogical principles for modernisation of the humanities education in China.Results and scientific novelty. Chinese education certification system has made notable progress in recent years. More universities and colleges are pursuing a quality improvement strategy focused on three main components – learning outcomes, student personality and continuous improvement. OBE establishes the same priorities; OBE is considered as a special type of effective pedagogical design. The features of this model implementation are briefly described – the structure of the training process, its stages and characteristics. The opportunities for improving humanities education based on OBE framework were considered. The OBE operates within the framework of the following core issues: the things students learn and the extent of student success, not the manner of learning; the place, the time of learning and the duration of training.OBE process implies ultimate involvement of students’ individual cognitive abilities to master competencies, which help adapt to future life. The knowledge of actual material (content of the programme) is not the key element of the education process, but the skills of knowledge application are important when solving specific tasks. The curricula, educational process, its methods, tools are adjusted, rebuilt and replaced if they do not contribute to the development of such skills, e. g. the results of the training determine its system and act not as a goal, but as a means of achieving it. The structure of results manages all educational activities, and their evaluation is carried out according to clear initially defined criteria, combined with flexible personalised requirements in order to get students to fully self-realise personal potential during a training course. To improve the initial design of curriculum, it is necessary to provide constant feedback “student-teacher”. The teacher has to organise and focus the learning process to give each student confidence in the acquired experience and to guarantee his or her success in further professional activities and life in general.Practical significance. The OBE concept fully complies with the needs and demands of modern society and modern people – it is no coincidence that such training has become one of the most popular forms of education in many countries, including the field of the humanities education in China. The present research leads to the conclusion that in the humanities field, notably in the teaching of foreign languages, a significant improvement in the quality of training of students can be achieved through the use of OBE teaching tools. In this model of training, practice is more important than theory. Moreover, this model assumes understanding to be more valuable than memory; the traditional “cramming” of educational information by students can be completely excluded; also, such model provides an opportunity to establish a continuous productive dialogue between the participants of educational process and to transform a classroom into a laboratory. The student becomes an active, self-motivated and responsible actor of his or her own individual educational trajectory, not a passive consumer of information, and the teacher – active assistant and coordinator of education.